Royalty as a Way to Protect Creator: Current Conditions in Indonesia: Royalti Sebagai Cara Melindungi Pencipta: Kondisi Saat Ini di Indonesia - Maddusila, Sitti Fatimah (Rechtsidee, 2022)
One of the legal rights that must be protected is intellectual property rights. This study analyzes intellectual property legal protection aspects based on a royalty system. This research is the normative legal research to produce legal arguments, usually called legal prescriptions. This study uses primary legal materials, which include: the 1945 Constitution of the Republic of Indonesia, the Patent Law, the Copyright Law, the Government Regulation on Song and/or Music Royalties, also the Plant Variety Royalties Act. Secondary legal materials include the results of studies and research on aspects of royalties in intellectual property rights. Non-legal material includes various non-legal studies of the royalty system in intellectual property. The approach in this research is a conceptual approach and a statutory approach. The results of the study confirm that the implication of the implementation of the royalty system in intellectual property rights requires the state to realize three fundamental legal values ​​related to royalty policies, such as guarantees of legal certainty over the rules regarding royalties, guarantees of benefit from the distribution of royalties, as well as guarantees of fair distribution of royalties based on the principle of proportionality. In addition, legal protection with a royalty system in intellectual property rights needs to be carried out externally and internally. Highlights: Royalty system needs legal certainty, benefits, and fair distribution. Fair distribution based on proportionality is important. External and internal legal protection is necessary. Keywords: Royalty, Intellectual Property Rights, Legal Value